Critical Synthesis Package: Medical Student Stressor Questionnaire (MSSQ) - Tammy Salazar (Association of American Medical Colleges, 2015)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Medical Student Stressor Questionnaire (MSSQ); and (2) a copy of the MSSQ instruments and manual and scoring guide developed by Muhamad Saiful Bahri Yusoff, MD. The purpose of the MSSQ is to identify sources of stress in medical students. Such sources include academic stressors, interpersonal stressors, teaching and learning stressors, social stressors, drive/desire stressors, and group activity stressors. The MSSQ is a self-report, self-scoring instrument with 40 items that ask students to rate the intensity of stress caused by each item on a 5-point Likert-type scale of 0-4 (0 = causing no stress, 4 = causing extreme stress). Preliminary validation studies indicate that the items are reliable and have a high level of internal consistency (Cronbach's alpha = 0.7). Factor analysis indicates that all items have construct validity and should be included in the survey. Confirmatory validation studies also yielded positive results with Cronbach's alpha of 0.9 or higher. One weakness of the MSSQ that the response statements on the MSSQ could be leading, and students may have a hard time distinguishing between levels (e.g., mild or moderate; moderate or high; high or severe). An additional weakness is that this measure has only been used with Malaysian medical students. Further research with US medical students is necessary to support its use in LCME-accredited schools. Strengths of the MSSQ include the fact that it has been used with consistent results across all levels of medical students (entering to graduating) and that it has the potential to design both school-wide wellness programs as well as individual interventions for students.